(Non)specific interaction patterns in families raising a child with disability or chronic illness: a latent profile analysis - Łada-Maśko, Ariadna; Sajewicz-Radtke, Urszula; Jurek, Paweł; Olech, Michał; Radtke, Bartosz M.; Lipowska, Małgorzata (Frontiers in Psychology, 2025)
IntroductionThe presence of a child with a disability significantly affects family dynamics introducing new responsibilities and altering roles. However, research also highlights the positive outcomes, such as increased family cohesion and stronger bonds among family members. Siblings face unique challenges, including emotional burdens and adjustment difficulties, which are influenced by factors such as age, severity of the disability, and parental attitudes. While some siblings develop empathy and nurture traits, others struggle with internalizing and externalizing problems. This study investigated whether families exhibit distinct interaction patterns based on the presence and type of a child’s disability, considering the perspectives of healthy siblings and parents.MethodsThe study comprised 179 dyads, each consisting of a healthy adolescent sibling of a child with a disability or chronic illness and one of their parents (N = 358). The sample included 49 families of children with diabetes, 49 with intellectual disabilities, 28 with motor disabilities, and 53 healthy children. To assess interaction patterns within families, the following measures were used: the Questionnaire of Relationships with Siblings to evaluate relationships between healthy adolescents and their siblings, the Parentification Questionnaire for Youth to measure emotional and instrumental parentification, the KidScreen-27 to assess quality of life, the Parental Attitude Scale-2 to assess parental attitudes, and the Family Rating Scales to evaluate family dynamics, including the structure and quality of family interactions. Latent Profile Analysis (LPA) was used to analyze data.ResultsWe identified two latent profiles: “Strained Families” profile, which featured lower-quality family interactions with parents displaying greater rejection, inconsistent, and overdemanding attitudes, and the “Resilient Families” profile reflected balanced functioning with greater cohesion and flexibility. The “Strained Families” profile was more prevalent (57%). No significant differences in profile frequencies were found across the groups.ConclusionBoth profiles included families with children with motor disabilities, intellectual disabilities, or diabetes and healthy children. Therefore, the results suggest that family interaction patterns varied independently of the presence of a child with a disability. Notably, 64% of the families with healthy children exhibited the “Strained Families” profile, marked by lower-quality interactions and family functioning, suggesting that such interactions are not exclusive to families of children with disabilities.